Adherencia terapéutica en pacientes con diabetes tipo 2 en un hospital general de zona - González Mondragón, Rocío (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
Background: Type 2 Diabetes is a public health problem, it is among the first 10 causes of death worldwide, second cause of death in Mexico, it is a frequent cause of disability in the young and economically active population. The factors associated with therapeutic adherence are mainly related to sociodemographic conditions; however, the health care team or system, the characteristics of the disease and the treatments also play a very important role. Objective: To identify the levels of therapeutic adherence in patients with type 2 diabetes at HGZ/MF No. 12. Material and Methods: Prospective, quantitative, observational, cross-sectional, descriptive study. Carried out from May 1 to October 31, 2022 in the population of IMSS beneficiaries, assigned to HGZ/MF No. 12 of Lázaro Cárdenas Michoacán, Mexico. The sample size was calculated for a finite population and a population of 4888 people was taken into consideration with an accepted estimation error of 0.05, and a sample of 100 participants was obtained. Patients of both sexes were included, whose age ranged from 20 to more than 60 years, with a diagnosis of type 2 diabetes, using the Martin Bayarre Grau test for data collection. Pregnant patients with a diagnosis of type I diabetes were not included, as well as those who did not agree to participate or who died during the course of the study. After evaluation of the protocol by the Local Ethics and Health Research Committee, the study was carried out. Results. A total of 100 patients affiliated to a family medicine unit were evaluated, and it was observed that 11 patients (11%) showed total therapeutic adherence to the treatment, while 77 patients (77%) showed partial adherence and 11 patients (12%) did not adhere to the treatment.

Antecedentes: La Diabetes tipo 2 es un problema de salud pública, se encuentra entre las primeras 10 causas de muerte a nivel mundial, segunda causa de muerte en México, es una causa frecuente de discapacidad en la población joven y económicamente activa. Los factores asociados a adherencia terapéutica son principalmente relacionados a condiciones sociodemográficas, sin embargo, también juega un papel muy importante el equipo o sistema de asistencia sanitaria, las características de la enfermedad y los tratamientos. Objetivo: Identificar los niveles de adherencia terapéutica en pacientes con diabetes tipo 2 del HGZ/MF No 12. Material y Métodos: Estudio prospectivo, cuantitativo, observacional, transversal, descriptivo. Llevado a cabo del 01 de mayo al 31 de octubre de 2022 en población derechohabiente del IMSS, adscrita al HGZ/MF No.12 de Lázaro Cárdenas Michoacán, México. Se hizo el cálculo del tamaño de la muestra para población finita y se tomó en consideración una población de 4888 personas con un error de estimación aceptado de 0.05, y se obtuvo una muestra de 100 participantes. Se incluyeron pacientes de ambos sexos, cuya edad osciló entre 20 y más de 60 años, con diagnóstico de Diabetes tipo 2. utilizando el test de Martin Bayarre Grau para recolección de datos. No se incluyeron pacientes embarazadas, con diagnóstico de Diabetes tipo I, así como los que no aceptaron participar o fallecieron durante el desarrollo de la investigación. Previa valoración del protocolo por el Comité Local de Ética e Investigación en Salud se procedió a realizar el desarrollo. Resultados. Se evaluaron 100 pacientes afiliados a unidad de medicina familiar, observa do que los que mostraron niveles de adherencia terapéutica total fueron 11 pacientes (11%) contra una adherencia parcial en 77 pacientes (77%) y no adheridos 11 pacientes (12%).
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: info:eu-repo/classification/cti/3; FCMB-E-2024-0157; Diabetes; Adherencia terapéutica; Tratamiento; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18748